Community Engagement Strategy of Posyandu Lily in Inorganic Waste Management Involving Parents - Ratuhasanah, Dhea; Erika, Masni Erika (Kiddie: Early Childhood Education and Care Journal, 2025)
Household inorganic waste remains environmental issue that has not been optimally addressed in Depok City. This study aims to describe the strategies employed by Posyandu Lily to encourage parental involvement in inorganic waste management programs. The research used a descriptive qualitative approach, with data collected through semi-structured interviews, routine activity observations, and documentation. The study was conducted over two months and involved five main informants: the head of the Posyandu, the head of the local waste bank, two parents, and one active community member. The findings indicate that Posyandu Lily plays a dual role—as a provider of health services and as a community-based environmental mobilizer. The waste bank operates biweekly, engaging both parents and children in weighing and depositing inorganic waste. Additionally, used cooking oil is collected and processed into soap, integrating environmental education with household economic value. Key supporting factors include proximity, environmental awareness, and direct benefits for families. The main obstacle is the lack of habit in sorting waste at home. The study concludes that Posyandu has the potential to serve as a center for family-based environmental empowerment if waste management activities are structured and inclusive.